Biología reproductiva de Pseudoplatystoma punctifer y Pseudoplatystoma tigrinum (siluriformes: pimelodidae) en la comunidad de Huapapa - cuenca baja del río Putumayo - Solsol Flores, Bianca Melanie (2022)
We carried out this work in the community of Huapapa – lower basin of Putumayo River, between November 20202 to October 2021. The main objective was, provide updated information about the reproductive biology of Pseudoplatystoma punctifer "doncella" and Pseudoplatystoma tigrinum "tigre zúngaro". 270 individuals of P. punctifer and 179 individuals of P. tigrinum were sampled, from the data obtained, it was determined that the sexual ratio of P. punctifer was 1.5:1, while which, for P. tigrinum was 0.9:1. The maturity size found for P. punctifer was 51.6 cm standard length for females and 53.2 cm standard length for males, while for P. tigrinum it was 61.4 cm standard length for females and 64.7 cm standard length for males. Regarding the reproductive season, the IGS values found indicate that it occurs between the months of November to March, beginning in the period of falling waters, reaching its maximum peak in the period of rising waters. According to the results obtained, we concluded that for P. punctifer there is a predominance of females over males, unlike P. tigrinum, which has a predominance of males, however, the difference found is not significant. The size at sexual maturity found indicates that these individuals are below known sizes. Recent research on this topic should taken into account, to observe the changes produced and to be able to take the necessary measures.